INTERETHNIC RELATIONS IN UZBEKISTAN: A CASE STUDY OF TURKEY - Ahmedova O'g'iloy (Scholar Express Journal, 2023)
This article explores the dynamics of interethnic relations in Uzbekistan, with a particular focus on the relationship between Uzbekistan and Turkey as a case study. Uzbekistan, known for its diverse ethnic makeup, has implemented inclusive policies to foster peaceful coexistence among its various ethnic communities. The Uzbek-Turkish relationship exemplifies the positive outcomes that can be achieved through cultural exchange, economic cooperation, and shared Turkic heritage. The article discusses the importance of promoting dialogue, equal opportunities, cultural preservation, and conflict resolution in maintaining harmonious interethnic relations. It also emphasizes the significance of international cooperation, youth engagement, and a strong sense of national identity. By implementing these measures, Uzbekistan can continue to strengthen its multiethnic society and serve as an example of successful interethnic relations
Keywords: Uzbekistan; interethnic relations; Turkey